Julie & Julia - Powell, Julie; Hachette Audio (Firm) (New York, N.Y. : Hachette Audio, 2009)
Thirty-year-old Julie Powell lives in a rundown apartment in Queens and works at a soul-sucking secretarial job that's going nowhere. Desperately needing something to free her from the monotony, she invents a deranged assignment: using her mother's dog-eared copy of Julia Child's 1961 classic Mastering the Art of French Cooking, Julia will cook all of the cookbook's 524 recipes within the span of one year.
Abridged.
Compact disc.
Produced and directed by Karen Pearlman ; text abridged by Karen DiMattia.
Read by and featuring a special conversation with the author.
Keywords: Child, Julia; Powell, Julie; Cooking, French -- Anecdotes; Women cooks -- Anecdotes